Preface - Agriculture, gender and COVID-19: Impact and recovery - Ringler, Claudia (All India Disaster Mitigation Institute (AIDMI), 2021)
I am honored to write the preface for the Southasiadisaster.net issue on “Agriculture, Gender and COVID-19: Impact and Recovery”. I started to engage with Self Employed Women’s Association (SEWA) in 2019 on a research-for-development project that was squarely focused on reaching women farmers with climate resilience strategies. We felt at that time that this was one of the most under-studied topics that was essential to rural women’s future in South Asia and elsewhere. I had no idea that the journey would lead to eventually trying to address key questions on the twin crises of climate change and COVID-19.